STUDI TAHAPAN PENANGANAN KASUS JEMAAT AHMADIYAH INDONESIA (JAI) - Aji Sofanudin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
This study aims to determine (1) the movement of the religious JAI, (2) how does the government policy stand against JAI. This study uses media reports of JAI in the mass media (kompas, republika, suara merdeka). The result, first, JAI is a religious organization based in Parung Bogor and is part of the International Ahmadiyya Community, based in London UK. The existence of JAI receives the refusal from Indonesian Moslems in forms of objection, disintegration, destruction of mosques including small mosques, and any assets of JAI in various regions. These events still occur even after 3 (three) years of SKB. Second, in dealing with JAI, the government made the following stages: (1) dialogue which involves the JAI and Islamic organizations, (2) Offer 7 Solutions to the JAI, (3) Requesting JAI to establish explanations that explains the doctrines they convey is entirely different with the alleged teachings (12 points of explanation from the PB JAI), (4) Ask for the government officials (Bakor Pakem) for monitoring, (5) Stating that JAI was not consistent, (6) Publish SKB, (7) Publish SE , (8) Socialization of SKB, and (9) Implementing missionary endeavor.